Menara Tabung Haji Tun Razak - Yusrizal, Muhammad Haziq Rizqi; Mohd Haniff, Nur Nadia Natrah; Mohd Sidik, Nur Syafiqah (2024)
The idea for the establishment of Perbadanan Wang Simpanan Bakal-Bakal Haji or Prospective Haji Savings Corporation (PWSBH) originated as a result of the proposal of a famous Malay economic figure, Professor Diraja Ungku Abdul Aziz bin Ungku Abdul Hamid, in December 1959 to the Federal Government of Malaya. Before the establishment of Lembaga Tabung Haji, there was no Islamic financial institution that could provide services to Muslims in Malaysia to save money to cover the cost of performing the Hajj. Although at that time there were already several banks, Muslims in this country refused to save with conventional banking for the purpose of performing the Hajj because they wanted to ensure that their savings were free from any elements and practices of riba so that the Hajj obtained was Hajj Mabrur. From September 30, 1963, PWSBH made history by opening a counter to receive savings from prospective pilgrims. Malaysian Muslims began to be educated to make savings from a young age to make savings with syariah-compliant organizations in preparation for the Hajj. In 1969, in order to strengthen its role and facilitate the coordination of the growing Hajj savings and management activities, PWSBH was merged with the Hajj Affairs Office which was established in 1951 and operates in Penang. This combined body was Lembaga Urusan dan Tabung Haji (LUTH), which was later changed lembaga tabung haji in 1995 or known as the abbreviation Tabung Haji or TH until now.